Development of the peanut precision fertilization control system based on threshold velocity algorithm - Fan, Yuqi; Yu, Yan; Shang, Shuqi; Gu, Tianying; Hu, Yanrui; Diao, Linsong; Ge, Ruchao; Zhang, Xing (International Journal of Agricultural and Biological Engineering, 2022)
In view of the fact that the current ground wheel velocimetry of the peanut precision fertilizer control system cannot solve the phenomenon of ground wheel slippage, and signal interference and delay loss cannot be excluded by BeiDou positioning velocimetry, a set of peanut precision fertilizer control system was designed based on the threshold speed algorithm. The system used STM32F103ZET6 microcontroller as the main controller, and touch screen for setting the operating parameters such as operating width, fertilizer type, and fertilizer application amount. The threshold speed algorithm combined with BeiDou and ground wheel velocimetry was adopted to obtain the forward speed of the tractor and adjust the speed of the DC drive motor of the fertilizer applicator in real time to achieve precise fertilizer application. First, through the threshold speed algorithm test, the optimal value of the length N of the ground wheel speed measurement queue was determined as 3, and the threshold of the speed variation coefficient was set to 4.6%. Then, the response performance of the threshold speed algorithm was verified by comparative test with different fertilization amounts (40 kg/hm2, 50 kg/hm2, 60 kg/hm2, 70 kg/hm2) under two speed acquisition methods of ground wheel speed measurement and threshold speed algorithm (combination of Beidou single-point speed and ground wheel speed measurement) in different operation speeds (3 km/h, 4 km/h, 5 km/h). The response performance test results showed that the average value of the velocimetry delay distance of the BeiDou single-point positioning velocimetry method was 0.58 m, while the average value of that with the threshold velocity algorithm was 0.27 m, which decreased by 0.31 m and indicated more accurate with the threshold velocity algorithm. The field comparison test for fertilizer application performance turned out an over 96.08% accuracy rate of fertilizer discharge by applied with the threshold speed algorithm, which effectively avoided the inaccurate fertilizer application caused by wheel slippage and raised the accuracy of fertilizer discharge by at least 1.2% compared with that of using the ground wheel velocimetry alone. The results showed that the threshold speed algorithm can meet the requirements of precise fertilizer application. Keywords: peanut, precision fertilizer planter, BeiDou velocimetry, ground wheel velocimetry, threshold speed algorithm, control system DOI: 10.25165/j.ijabe.20221505.7342 Citation: Fan Y Q, Yu Y, Shang S Q, Gu T Y, Hu Y R, Diao L S, et al. Development of the peanut precision fertilization control system based on threshold velocity algorithm. Int J Agric & Biol Eng, 2022; 15(5): 116–122.